Association of peripheral inflammatory cytokines with motor and non-motor symptoms in patients with Parkinson’s disease and type 2 diabetes mellitus - Aiping Hu; Yuqing She; Xue Cao; Yang Wang; Shu Wu; Juan Lu; Yang Zhao; Lizhi Yu; Haifeng Jiang; Qing Chen (Frontiers in Neurology)
ObjectiveThis pilot study aims to investigate the association between peripheral inflammatory cytokines and motor and non-motor symptoms in patients with both Parkinson’s disease (PD) and type 2 diabetes mellitus (T2DM) and the underlying mechanisms.MethodsSixty patients with PD were divided into two groups depending on whether they also had T2DM, resulting in a PD group (21 cases) and a PD–T2DM group (39 cases). Thirty healthy volunteers from the physical examination centre were enrolled as the control group. Peripheral blood was collected from all patients.ResultsPatients with PD–T2DM had higher Movement Disorders Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) III scores; total MDS-UPDRS scores; Parkinson’s Disease Questionnaire-39 (PDQ-39) scores; and interleukin (IL)-6, IL-1β, tumour necrosis factor alpha (TNF-α) and IL-4 levels than patients with PD (p < 0.05). In the PD group, IL-4 levels correlated with UPDRS II (r = 0.337), Non-Motor Symptom Scale (r = 0.354), Hamilton Depression Scale (r = 0.420) and PDQ-39 (r = 0.423) scores (p < 0.05). A multivariate regression revealed IL-6 independently predicted lower UPDRS III scores (β = −0.497, p = 0.018), TNF-α correlated with PD duration (β = 0.689, p < 0.001) and IL-1β correlated with PDQ-39 scores (β = 0.462, p = 0.002) in patients with PD–T2DM. Adjusted models explained up to 52.3% of variance (adjusted R2). In the PD group, age-adjusted correlations confirmed IL-4 was associated with UPDRS II (r = 0.321, p = 0.047) and PDQ-39 (r = 0.418, p = 0.009), and interferon gamma (IFN-γ) was associated with Scales for Outcomes in Parkinson’s Disease-Autonomic Questionnaire (SCOPA-AUT; r = −0.564, p = 0.001). Negative correlations were identified between IL-6 and UPDRS III scores (r = −0.497) and IFN-γ and SCOPA-AUT scores (r = −0.588; p < 0.05).ConclusionThese pilot findings suggest peripheral inflammatory cytokines can be considered biomarkers in patients with PD–T2DM. The underlying mechanism by which T2DM worsens the motor and non-motor symptoms of PD may involve increased inflammation.